Cultural seeds [ essays on the work of Nick Cave - Dalziell, Tanya , 1973-; Welberry, Karen (Ashgate popular and folk music series, 2009)
Nick Cave is now widely recognized as a songwriter, musician, novelist, screenwriter, curator, critic, actor and performer. From the band, The Boys Next Door (1976-1980), to the spoken-word recording, The Secret Life of the Love Song (1998), to the recently acclaimed screenplay of The Proposition (2005) and the Grinderman project (2008), Cave's career spans thirty years and has produced a comprehensive (and sometimes controversial) body of work that has shaped contemporary alternative culture. Despite intense media interest in Cave, there have been remarkably few comprehensive appraisals of hi.